To Whom Do We Publish, and Who Truly Benefits? - Yusuf, Saldy (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Research is an integral part of healthcare professionals' activities, including nursing. Clinical processes such as anamnesis, physical examinations, and laboratory data collection are routine procedures and fundamental mechanisms for gathering evidence-based data to support clinical decision-making. These data are subsequently analyzed to assess patient progress—whether improving, stagnating, or deteriorating. Hospitals and healthcare facilities use continuous data collection in everyday clinical practice. However, a critical question arises: To what extent does this data effectively address patient issues? Is data collection genuinely aimed at improving patient care, or is it primarily conducted to fulfill educational requirements for students and research objectives for academics?